Measuring the learning effectiveness of two courses in a program in accounting data and analytics - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2023)
Driven by rapid technological innovation, information technology (IT) is expected to significantly alter the way that accountants work. However, both accounting researchers and practitioners have observed a shortage of accounting professionals who currently possess the relevant technology skillsets to exploit technological advances. In response, the School of Accountancy of a Singapore-based university launched a second major program in Accounting Data and Analytics in 2018. In this study, we examine the learning effectiveness of two courses – Business Data Management and Data Modelling & Visualization – offered as part of the program. Overall, our results suggest that the courses are effective in enhancing the learning of participants in the areas of business data management, data modelling, and data visualization. These findings are important to students, educators, and employers.